Adaptations to alpine and polar environments in insects and other terrestrial arthropods - Sømme, Lauritz; Block, William (Insects at low temperature, 1991)
Keywords: Antarktis; ekspedisjoner; insekter; kuldetoleranse; polarområdene; virvelløse dyr

Ecological studies on Cryptopygus sverdrupi from Muhlig-Hofmannfjella, Antarctica - Sømme, Lauritz (Cryo-Letters, 1985)
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; zoologi; økologi

Adaptation to low temperature in Antarctic terrestrial arthropods - Sømme, Lauritz (Comite National Francais Des Recherches Antarctiques, 1982)
Pages: 219-225 Publication Title: Colloque sur les ecosystèmes subantarctiques Volume: 51 Place: Station Biologique de Paimpont, Université de Rennes, France
Keywords: Antarktis; ekspedisjoner; forskning; kuldetoleranse; virvelløse dyr

Studies of arthropod cold hardiness - Block, William; Sømme, Lauritz (British Antarctic Survey Bulletin, 1981)
Keywords: Antarktis; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Kuldetoleranse hos alpine og arktiske collemboler - Sømme, Lauritz (Entomologisk tidskrift, 1978)
Keywords: Antarktis; ekspedisjoner; entomologi; forskning; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Notes on the cold-hardiness of prostigmate mites from Vestfjella, Dronning Maud Land - Sømme, Lauritz (Norwegian Journal of Entomology, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; kuldetoleranse; midder; miter; virvelløse dyr; zoologi

Field studies on the effect of cold on man, with special reference to metabolic rate - Wilson, Ove (C.W.K. Gleerup, 1966)
Resyme av dr.avh. - 7 enkeltskr. ib. med resymeet
Publication Title: Acta Universitatis Lundensis
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; fysiologi; kuldeeksponering; kuldetoleranse; medisin

Man in Antarctica - Rodahl, Kaare (Science in Antarctica. Part 1: The Life sciences in Antarctica, 1961)
Keywords: Antarktis; ekspedisjoner; forskning; fysiologi; kuldetoleranse; medisin; polarområdene

Basal metabolic rate in the Antarctic - Wilson, Ove (Metabolism: Clinical and Experimental, 1956)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; fysiologi; kuldetoleranse; medisin